2011
DOI: 10.1002/humu.21428
|View full text |Cite
|
Sign up to set email alerts
|

Massive parallel amplicon sequencing of the breast cancer genes BRCA1 and BRCA2: opportunities, challenges, and limitations

Abstract: This study describes how the new massive parallel sequencing technology can be implemented in a diagnostic setting for the breast cancer susceptibility genes (BRCA1 and BRCA2). The throughput was maximized by increasing uniformity in coverage, obtained by a multiplex approach, which outperformed pooling of singleplex PCRs. We evaluated the sensitivity by analysis of 133 distinct sequence variants; three (2%) deletions or duplications in homopolymers of greater than or equal to seven nucleotides remained undete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
2

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 26 publications
5
67
0
2
Order By: Relevance
“…This result outperforms the homogeneity previously reported by other groups describing next-generation BRCA testing using either longrange PCR, 4 primer-specific direct capture for single-molecule sequencing, 13 or in-house single/multiplex PCR. 12,14 It is also important to note that all of the MIDs used in the present study showed similar coverage results. Overall, this commercial assay allows the generation of a robust library for all the patients under study, maximizing the number of samples analyzed in a run.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…This result outperforms the homogeneity previously reported by other groups describing next-generation BRCA testing using either longrange PCR, 4 primer-specific direct capture for single-molecule sequencing, 13 or in-house single/multiplex PCR. 12,14 It is also important to note that all of the MIDs used in the present study showed similar coverage results. Overall, this commercial assay allows the generation of a robust library for all the patients under study, maximizing the number of samples analyzed in a run.…”
Section: Discussionsupporting
confidence: 64%
“…The main disadvantage of pyrosequencing relative to other NGS technologies is the accuracy of length determination in homopolymers. 12,17,21 In pyrosequencing, the light-intensity signal observed in each cycle is proportional to the actual number of incorporated nucleotides, which is the base for homopolymer length calling. The accuracy of this method decreases with homopolymer length, which may eventually generate artefactual insertions and deletions in long homopolymers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations